The correlation between body mass index and intraocular pressure in children without Down syndrome and children with Down syndrome - Rizqillah, Aliyah Faiza; Wulandari, Lely Retno; Dewi, Nadia Artha; Anandita, Nanda Wahyu (Medical Faculty of Brawijaya University, Indonesia, 2024)
Background: Intraocular Pressure (IOP) is the fluid pressure in the eye. Primarily, IOP is influenced by the production and drainage of aqueous humor. The IOP value is in the normal range if the production and drainage of aqueous humor are balanced so that IOP homeostasis must be maintained. Eye dysfunction can occur if the production and drainage of aqueous humour are not balanced. IOP can be influenced by factors such as Body Mass Index (BMI). This study aims to find out whether there is a correlation between BMI and IOP in children without Down syndrome and children with Down syndrome, where children with Down syndrome have one of the eye manifestations in the form of steep and thin corneas which could be one of the factors causing affect the results of IOP measurements. Methods: The research method used is quantitative-observational with a cross-sectional approach. The total research sample used in this study was 101 children aged 0 to 18 years, with details of 79 children without Down syndrome and 22 children with Down syndrome. Data were processed using the Mann-Whitney hypothesis test and T-test, as well as the Spearman correlation test. Results: The results of the study showed that there was a difference in IOP between children without Down syndrome and children with Down syndrome (p < 0.1), there was a difference in BMI results on IOP in children without Down syndrome and children with Down syndrome (p < 0.1), and there was no correlation between BMI and IOP in children without Down syndrome (p > 0.1). It was found that there was a correlation between BMI and IOP in children with Down syndrome (p < 0.1). It was stated that BMI contributed 91.7% to the increase in IOP. Conclusion: there was a significant difference in IOP and BMI results on IOP between children with and without Down syndrome. There was no correlation between BMI and IOP in children without Down syndrome, but there was a correlation between BMI and IOP in children with Down syndrome.